Mindfulness: A Missing Integral Component of Leadership Preparation Programs - Pedro J. De La Cruz Albizu; Gerald Maraia (Merits, 2025)
This essay argues for the inclusion of mindfulness training in educational leadership preparation programs in the United States. Educational leaders have a determining influence on school effectiveness, and their success depends on the quality of the preparation they receive. As such, increased attention to school leadership and school leader preparation has emerged, and important efforts to improve the preparation of school leaders have been undertaken, including the development of the National Educational Leadership Preparation standards. However, while the standards are extremely valuable, they concentrate on what leaders know and do for others, not on their well-being, who they are, or how they determine what to do. Hence, the standards may contribute to the increasingly technocratic orientation in the narrative about and preparation of educational leaders. While such orientation supports the development of necessary knowledge and skills, it may leave gaps in relational and internal capacities; capacities that have been identified as increasingly important for today’s school leaders, not just for their job performance, but also for their well-being and longevity on the job. This essay highlights some of the ways in which mindfulness can support the preparation of school leaders while enhancing their relational, internal, and standards-based capacities.